Relation of Plasma Fibrinogen Level With the Presence, Severity, and Complexity of Coronary Artery Disease. (September 2017) - Tabakcı, Mehmet Mustafa; Gerin, Fethullah; Sunbul, Murat; Toprak, Cuneyt; Durmuş, Halil İbrahim and Demir, Serdar and Arslantaş, Uğur and Cerşit, Sinan and Batgerel, Ulaankhuu and Kargın, Ramazan
Background: Relation of plasma fibrinogen levels with extent, severity, and complexity of coronary artery disease (CAD) in patients with stable angina pectoris (SAP) has not been adequately investigated. The aim of this study was to evaluate whether plasma fibrinogen level is associated with coronary complexity, severity, and extent assessed by SYNTAX (Synergy between percutaneous coronary intervention with TAXUS and Cardiac Surgery) score (SS). Methods: We enrolled 134 consecutive patients with SAP who underwent coronary angiography. Baseline serum fibrinogen levels were measured, and SS was calculated from the study population. The patients were classified into 3 groups by tertiles of SS (SS, control group = 0; intermediate group < 22; and high group ≥ 22). Results: Plasma fibrinogen levels demonstrated a stepwise increase from control group to high SS group. There was a strong correlation between fibrinogen and the SS ( r = .535, P < .001). Area under the receivers operating characteristic curve of fibrinogen was 0.72 (95% confidence interval [CI] 0.61-0.82; < .001) for predicting a high SS. Fibrinogen value higher than 411 mg/dL has a sensitivity of 75% and a specificity of 64% in prediction of high SS. In multivariate analyses, plasma fibrinogen was observed to be an independent predictor for high SS in patients with stable CAD (odds ratio [OR] 1.01; 95% CI, 1.01-1.02; P < .001). Conclusion: Plasma fibrinogen is a readily measurable systemic inflammatory marker and is independently associated coronary severity and complexity in patients with CAD.